Research on high-resolution processing of frequency modulation combined signal for active sonar detection - Jia, Yaojun; Wang, Pingbo; Wei, Hongkai; Chen, Qiang; Hu, Yunhua (Frontiers in Physics, 2025)
The Frequency Modulation Combined (FMC) waveform has delay (range)-Doppler (velocity) coupling resolution, and the traditional nonlinear high-resolution algorithms represented by Point-wise Product (PP) and Point-wise Minimization (PM) have good anti-reverberation performances, but their detection performances are poor under low Signal-to-Noise Ratio (SNR) conditions. We propose the improved method PAMP by combining PP and PM methods, and select the combination waveform of “W”-type Linear Frequency Modulation (W-LFM) as the processing object, verifying the effectiveness of the proposed method through numerical simulation and lake experiment. Firstly, the ROC curve analysis shows that the detection performance of PAMP is significantly improved compared with PM and PP, and is close to the optimal detector. Secondly, numerical simulation shows that PAMP is more suitable for target detection in low SNR scenario, where it has a narrower resolution width and lower reverberation energy. Finally, we design lake experiment and analyze the data processing results. The active sonar display image in direction-velocity-range coordinates demonstrates the high-resolution advantage of the FMC signal represented by W-LFM. Moreover, PAMP effectively reduces the intensity of reverberation area and improves the range-velocity resolution, realizing the high-resolution detection for active sonar.